A study on prescribing pattern of medications for chronic disorders in community setting - James, Jennifer; Krishna, Mahima H.; M. D., Mahima Prakash; Panyala, Sai Meenakshitha; Kumar, B. R. Jaidev (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Non-communicable diseases (NCDs) or chronic disorders are preventable and costly conditions which are a leading cause of mortality worldwide. Monitoring and evaluating prescribing patterns provide crucial insights into current medication trends, usage, and emerging practices, informing necessary modifications. Methods: This was a prospective cross-sectional observational study conducted over six months in community pharmacies in Mysuru. Patients diagnosed with chronic disorders who visited community pharmacies and who met the study criteria were enrolled. Data was collected from prescriptions, patient/caretaker interviews, medical records, and medication strips. Disorders were classified using ICD-10, and drugs were classified based on ATC classification to assess prescribing patterns. Results: A total of 511 patients were enrolled, with a mean age of 56.4 years and a male predominance. Diseases of the circulatory system were the most common, followed by endocrine, nutritional, and metabolic diseases. Cardiovascular system drugs were most frequently prescribed, followed by those for the alimentary tract and metabolism. The most common comorbidity was T2DM with HTN. Conclusions: Prescribing patterns for chronic diseases vary across regions in south India. In chronic disorders, where patients are on lifelong medication, patient adherence, counselling on potential side effects and correct medication usage are essential. This study highlighted the need for continuous monitoring of prescribing practices to ensure optimal patient outcomes and rational drug use in community settings.